Relatório de Estágio Profissional "De aluno a professor: O realizar de um sonho" - Sérgio Leandro Ferreira Nogueira (2017)
The traineeship represents the ultimate step in initial training. At this stage the student trainee applies in real context all the theoretical and practical knowledge acquired throughout his/her training, so he/she is confronted for the first time with reality. The challenges are huge and the demand is maximum. By performing the tasks inherent to his/her profession, the experiences within the school community and the reflection about his/her practice, the student trainee will develop the skills required for a quality teaching. This training report course aims to portray the path travelled throughout the school year and it is divided into 7 chapters: he first chapter is the "Introduction"; the second chapter relates to "Personal Framework" in which I identify myself and I speak a little bit about my sports and academic experiences as well as the reasons which led me to join this area; the third chapter, "Institutional Framework", explains the context in which the traineeship was carried out and presents the internship group, the resident class and the shared class; the fourth chapter, "Performance", mirrors the organization and management of the teaching-learning process, highlighting the problems, difficulties and strategies adopted; the next chapter is called "Participation in School and Relationship with the Community", and this covers the school activities and the relationship established with the school community; Chapter six is called "Research-Action Study"; and, finally, chapter seven refers to the "Final Considerations and Future Perspectives".